The Relationship Of Knowledge And Attitude Of The Elderly About Diet To Prevention Of Hypertension In Hutasoit I Village Lintongnihuta District, Humbang District The Hasundutan Year 2023 - Benni Maria LumbanToruan; Lidia Silaban; Rouli D.F Simamora (CV. AFDIFAL MAJU BERKAH, 2023)
Diet is one of the human behaviors that is carried out every day in meeting the needs in dealing with hypertension sufferers so they can control their habits. This study aimed to determine the relationship between the knowledge and attitudes of the elderly about diet and the prevention of hypertension. This type of research is quantitative analytic research with a cross-sectional design. This research was conducted in April-July 2023. In Hutasoit I Village, Lintong Nihuta District. The population is elderly in Hutasoit I village, 70 people. The accidental sampling technique was taken and used the Slovin and Chi-square formulas with a total sample of 41 people. The results showed that there was a relationship between the elderly's knowledge about diet and the prevention of hypertension with a confidence level of 90% and df = 2, which obtained a chi-square count of 10.812 > chi-square table of 4.605. The attitude variable has a relationship with the prevention of hypertension by using chi-square with a confidence level of 90% and df = 1 obtained chi-square count 8.744 > chi-square table 2.705. It is expected that the respondents will get more information to increase their knowledge and attitudes in increasing the level of health regarding diet towards the prevention of hypertension